2020
DOI: 10.3390/w12092621
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development, and Performance Evaluation of a Fertigation Device for Distributing Solid Fertilizer

Abstract: Solid fertilizers, which have a low operating cost, are widely applied in Chinese crop fields. In order to distribute solid fertilizer through fertigation, an innovative device with a simple structure was designed, which can feed, dissolve, and distribute fertilizer simultaneously. The parameters of the outlet pipe and fertilizer-feeding component were designed, and a preliminary equation for calculating the fertilizer-feeding flowrate was established. Then experiments were conducted to optimize the establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Li et al [24] analyzed the structure principle and main performance parameters of a fertilization pump, and also carried out a hydraulic performance test, indicating that the injection ratio of the fertilization pump was relatively stable under different inlet and outlet pressure differences. Zhang et al [25] designed an innovative piece of equipment with a simple structure to distribute solid fertilizer through a fertigation system. In actual engineering applications, Bracy [26], Tayel [27] and Li [11,15] successfully applied a PI as one kind of injector to inject fertilizer into irrigation water and indicated that the use of a PI can result in good water and fertilizer distribution uniformity because of the high injection precision of the Venturi injector.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [24] analyzed the structure principle and main performance parameters of a fertilization pump, and also carried out a hydraulic performance test, indicating that the injection ratio of the fertilization pump was relatively stable under different inlet and outlet pressure differences. Zhang et al [25] designed an innovative piece of equipment with a simple structure to distribute solid fertilizer through a fertigation system. In actual engineering applications, Bracy [26], Tayel [27] and Li [11,15] successfully applied a PI as one kind of injector to inject fertilizer into irrigation water and indicated that the use of a PI can result in good water and fertilizer distribution uniformity because of the high injection precision of the Venturi injector.…”
Section: Introductionmentioning
confidence: 99%